Martuppak Tradition in The Marriage of Mandailing Tribe in Pasaman District from The Perspective of Islamic Law - Reski, M.; Hafsah, Hafsah; Tanjung, Dhiauddin (Law Development Journal, 2024)
This research is motivated by the Mandailing tribe in Pasaman Regency considers that the practice of the Martuppak tradition is a form of debt and credit that is carried out when they want to hold a marriage. Then in the practice of the Martuppak tradition there is an obligation for someone to pay back the money that has been given. This is the cause and effect of the Martuppak tradition practice system, there is a reciprocal relationship between the giver of tuppak money and the recipient of tuppak money. Martuppak is giving some money to someone or to the suhut and then must be returned based on the amount given with an additional amount of at most 10% and at least 1% (sincerely). Therefore, researchers are interested in researching the problem, as for the formulation of the problem in this study is first, how is the implementation of the Martuppak tradition at the Mandailing tribe community marriage in Pasaman Regency. Second, what are the views of religious leaders, traditional leaders and the people of Pasaman Regency about the Martuppak tradition, third, how is the legal analysis of the Martuppak tradition at the Mandailing tribe community marriage in Pasaman Regency in the perspective of Islamic law? The aims of this research is to find out how the implementation of the Martuppak tradition at the Mandailing tribe community marriage in Pasaman Regency. To find out how religious leaders, traditional leaders and the people of Pasaman Regency view the Martuppak tradition and to find out the legal analysis of the Martuppak tradition at the Mandailing tribe's marriage in Pasaman Regency in the perspective of Islamic law. The method used is field research using interview techniques, then the data is analyzed using qualitative descriptive analysis methods. From the results of the analysis that the author conducted on the data, it can be concluded that every debt and credit that contains benefits is usury, and everything that contains usury is forbidden. Therefore, the Martuppak tradition practiced by the Mandailing tribe in Pasaman Regency is included in debts and credits that contain benefits and the tradition is a fasid tradition.